Regador: APP for coffee water potential estimation - Silva, Patricia Costa; Souza, Vanessa Cristina Oliveira; Volpato, Margarete Marin Lordelo; Silva, Vania Aparecida (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
In coffee farming, reductions in water availability decrease productivity. Therefore, monitoring the water potential (Ψ), a measure that assesses whether a plant is under water stress, helps management. This article presents the design, development and evaluation of a georeferenced mobile application for coffee farming water potential in the south of Minas Gerais. This work was developed with the premises of Design Science. In particular, in the development of an IT artifact. The research was prescriptive and the artifact was generated as a proof of concept of the system. The analysis of the results was carried out with a quantitative approach. The evaluation of user satisfaction carried out with researchers and coffee growers obtained satisfactory results and validates the importance of the application developed in the decision-making process in the field. The impact is both in the technical and business spheres, since the article contemplates the methodology for developing an artifact that aims to bring scientific research and rural producers closer, as it materializes a model currently available only in specialized journals.